2002
DOI: 10.1046/j.1532-5415.2002.50115.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Psychological Distress in Community‐Dwelling Older Adults

Abstract: OBJECTIVES-To examine the relationship between urinary incontinence (UI) and psychological distress in older adults. We hypothesized that persons with UI associated with condition-specific functional loss would be most likely to report psychological distress. DESIGN-A population-based longitudinal survey. SETTING-Continuing participants in a study of community-dwelling adults who were initially living in East Baltimore in 1981.PARTICIPANTS-Persons aged 50 and older (n = 781) at follow-up interviews conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 38 publications
7
68
0
1
Order By: Relevance
“…Sample Size estimated after doing a thorough Review of Literature where it was found that the prevalence ranges from 0-60%. [6][7][8][9][10][20][21][22][23][24] Taking a mean prevalence as 30%, relative error of 20% of p. Using Formula: N = z²pq/L², we got the sample size as 233. Taking design effect of 2 and applying non-response rate of 5 %, we finally took a sample size of 530 postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample Size estimated after doing a thorough Review of Literature where it was found that the prevalence ranges from 0-60%. [6][7][8][9][10][20][21][22][23][24] Taking a mean prevalence as 30%, relative error of 20% of p. Using Formula: N = z²pq/L², we got the sample size as 233. Taking design effect of 2 and applying non-response rate of 5 %, we finally took a sample size of 530 postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
“…8 Elderly women are the most affected, with a mean prevalence of 34%. 9 Women suffering from urinary incontinence constitute about 70-80% of female patients reporting to a physician due to urinary system diseases. 10 It is estimated that 25-45% of women of different ages have involuntary urine loss and 9-39% of women over 60 years report daily urinary leakage.…”
Section: Introductionmentioning
confidence: 99%
“…In the conventional scoring of the GHQ, a score of 4 or more indicates psychological 'caseness' (e.g. 10,34,35). In these analyses, we treated GHQ scores as continuous variables.…”
Section: Measurement Strategymentioning
confidence: 99%
“…This is a critical gap because psychiatric conditions are a major contributor to disability [16]. Previous studies have suggested an association between urinary incontinence and depression [17][18][19][20][21][22][23]. In addition, some authors have found an association between elevated scores on anxiety scales and urinary incontinence [17,24].…”
Section: Introductionmentioning
confidence: 99%